(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background Cardiac arrhythmias remain among the most important early complications of acute myocardial infarction despite advances in reperfusion therapy and coronary care management. The first 24 hours following ST-elevation myocardial infarction (STEMI) represent the period of greatest electrical instability and highest risk of sudden cardiac death. Objectives: To evaluate the incidence and spectrum of arrhythmias occurring within the first 24 hours of STEMI and to analyze their association with infarct territory, left ventricular ejection fraction (LVEF), and in-hospital outcomes. Methods: This prospective observational study included 150 consecutive patients with confirmed STEMI admitted to a tertiary care teaching hospital in Central India. Continuous ECG telemetry monitoring was performed during the first 24 hours after admission. Arrhythmias were categorized as ventricular arrhythmias, supraventricular arrhythmias, and conduction abnormalities. Associations between arrhythmias, infarct territory, ventricular function, and short-term outcomes were analyzed. Results: The mean age of the study population was 59.51 ± 12.44 years, and 82.7% were male. Arrhythmias occurred in 72.0% of patients during the first 24 hours following STEMI. Ventricular premature complexes were the most common arrhythmia (41.3%), followed by sinus tachycardia (21.3%), atrial premature complexes (14.7%), first-degree atrioventricular block (12.7%), and sinus bradycardia (11.3%). Ventricular tachycardia and ventricular fibrillation occurred in 6.0% and 3.3% of patients, respectively. Anterior wall STEMI showed significant association with arrhythmia occurrence (p<0.05), whereas inferior wall STEMI was associated predominantly with bradyarrhythmias and atrioventricular conduction disturbances (p<0.01). Arrhythmia incidence increased progressively with worsening ventricular dysfunction (p<0.001). LVEF <40% emerged as an independent predictor of arrhythmias (OR 5.56, 95% CI 2.15–14.36; p<0.01). Overall in-hospital mortality was 12.7%. Conclusion: Cardiac arrhythmias remain highly prevalent during the first 24 hours following STEMI and continue to contribute significantly to early morbidity and mortality. Infarct territory and left ventricular dysfunction are major determinants of arrhythmia burden and adverse clinical outcomes. Continuous ECG monitoring remains essential for early risk stratification and timely intervention.